Pengaruh Intellectual Capital, Biaya Intermediasi dan Islamicity Performance Index Terhadap Profitabilitas Syariah di Indonesia - Bustamam Bustamam; Dhenni Aditia (Jurnal Dinamika Akuntansi dan Bisnis, 2016)
This study aimed to examine effect of intellectual capital, cost of intermediation, and islamicity performance index on profitability of Islamic Banks Indonesia. Data was collected from financial reports of 44 Islamic Banks that are registered in Indonesian Central Bank.  The period of study was between 2011 and 2014. The analysis technique used was multiple linear regression.This study found that collectively the cost of intermediation, and islamicity performance index have an influence for profitability. Meanwhile, in the partial test (t test), variable intellectual capital, the cost of intermediation, and islamicity performance index have determined profitability of the Islamic banks.